Relationship between life style and metabolic control among patients with type 2 diabetes in Chota, Peru - Asenjo-Alarcón, José Ander (2020)
Objective: To determine the relationship between life style and metabolic control among patients with type 2 diabetes in Chota, Cajamarca. Methods: cross sectional study among 102 patients at Centro Médico de EsSalud. Life style was determined using the IMEVED questioner, and metabolic control was evaluated with a guideline adapted from the American Diabetes Association (ADA). Relative and absolute frequencies were calculated, chi square and the gamma coefficient with a 95% level of confidence were used. Results: Unfavorable life style was observed in 45.1%, overweight in 43.1%, increased abdominal perimeter in 53.9%, hyperglycemia in 62.7%, high C-LDL in 79.4%, reduced C-HDL in 59.8%, high triglycerides in 61.8% and bad metabolic control in 61.8%. Conclusions: Most patients had an unfavorable life style, a direct relationship between life style and metabolic control was found. An unfavorable life style was associated with poor metabolic control.